2001
DOI: 10.1002/1097-4652(2000)9999:999<000::aid-jcp1036>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the components of the 150 kDa IGF binding protein complex in cocultures of rat hepatocytes and Kupffer Cells by 3?,5?-cyclic adenosine monophosphate

Abstract: In the circulation, most of IGFs are bound to a high molecular mass complex of 150 kDa that consists of IGF-I (or IGF-II), IGFBP-3 and the acid-labile subunit (ALS). Within rat liver, biosynthesis of these components has been localized to different cell populations with hepatocytes as source of ALS and nonparenchymal cells (endothelial and Kupffer cells (KC)) as source of IGFBP-3. In the present study, the regulatory effects of the cAMP analogs dibutyryl-cAMP (db-cAMP) and 8-bromo-cAMP (8-br-cAMP) on IGF-I, AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Although released from diVerent cellular sources within rat liver, biosynthesis of the individual components of the 150 kDa complex was apparently controlled by the same regulatory mechanism. Maintenance of cocultures of hepatocytes with KCs in the presence of cAMP decreased the biosynthesis of IGFBP-3 (released from KCs) and ALS (released from hepatocytes) synergistically, 19 whereas insulin treatment resulted in a synergistic stimulation of the biosynthesis of these components. 30 This synergistic regulation might be facilitated by a cellular interaction between hepatocytes and KCs because a soluble factor secreted by hepatocytes was necessary for the stimulated IGFBP-3 biosynthesis in KCs in response to insulin.…”
Section: Igfbpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although released from diVerent cellular sources within rat liver, biosynthesis of the individual components of the 150 kDa complex was apparently controlled by the same regulatory mechanism. Maintenance of cocultures of hepatocytes with KCs in the presence of cAMP decreased the biosynthesis of IGFBP-3 (released from KCs) and ALS (released from hepatocytes) synergistically, 19 whereas insulin treatment resulted in a synergistic stimulation of the biosynthesis of these components. 30 This synergistic regulation might be facilitated by a cellular interaction between hepatocytes and KCs because a soluble factor secreted by hepatocytes was necessary for the stimulated IGFBP-3 biosynthesis in KCs in response to insulin.…”
Section: Igfbpsmentioning
confidence: 99%
“…In fact, when cocultures of hepatocytes with KCs were incubated at pH 7.4 and 37°C in the presence of iodinated IGFBP-3, a time dependent disappearance of intact IGFBP-3 and the generation of several IGFBP-3 proteolytic fragments of diVerent sizes was observed. 19 This indicated that, after endocytosis, a cathepsin mediated proteolysis of IGFBP-3 in intracellular organelles occurs, accompanied by partial recycling and release of IGFBP-3 fragments into the extracellular medium. The process of endocytosis and subsequent proteolytic degradation of IGFBP-3, as demonstrated in the coculture model with hepatocytes and KCs, might reflect the capacity of the liver to clear IGFBP-3 from the circulation.…”
Section: Igfbp Proteasesmentioning
confidence: 99%
“…Although Igf1 and Igfbp3 genes in the liver are positively regulated by GH, other stimuli differentially affect them. For example, in cocultures of rat hepatocytes and Kupffer cells cAMP decreases Igfbp3, whereas it increases Igf1 biosynthesis (Scharf et al 2001). Furthermore, glucocorticoids inhibit Igf1, whereas they increase Igfbp3 mRNA in the liver (Luo & Murphy 1990, Koedam et al 2000, Priego et al 2005b.…”
Section: Discussionmentioning
confidence: 99%